Inraoperative and Histological Visualization of Disrupted Vulnerable Plaques following Diagnostic Angiography of Moderate Carotid Stenosis - Tatsushi Mutoh; Tatsuya Ishikawa; Akifumi Suzuki; Nobuyuki Yasui (Stroke Research and Treatment)
Background. Digital subtraction angiography (DSA) remains an important tool for diagnosis of carotid stenosis but is associated with risk for periprocedural complications. This is the first report of direct intraoperative and histolopathologic visualization of DSA-related carotid plaque disruption. Case. A 64-year-old man diagnosed to have a 60% right carotid stenosis received diagnostic DSA for therapeutic decision-making. He developed transient left hand numbness and weakness immediately after the procedure. Intraoperative imaging during carotid endarterectomy revealed a fragile plaque with sharp surface laceration and intraplaque hemorrhage at the bifurcation. Microscopy of the specimen demonstrated a large atheromatous plaque with fibrous hypertrophy and intraplaque hemorrhage filled with recent hemorrhagic debris. Conclusion. The visualized carotid lesion was more serious than expected, warning the danger of embolization or occlusion associated with the catheter maneuvers. Thus the highest level of practitioner training and technical expertise that ensures precise assessment of plaque characteristics should be encouraged.